2006
DOI: 10.1128/aem.72.1.522-526.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stable Concentrated Emulsions of the 1-Monoglyceride of Capric Acid (Monocaprin) with Microbicidal Activities against the Food-Borne Bacteria Campylobacter jejuni , Salmonella spp., and Escherichia coli

Abstract: Of 11 fatty acids and monoglycerides tested against Campylobacter jejuni, the 1-monoglyceride of capric acid (monocaprin) was the most active in killing the bacterium. Various monocaprin-in-water emulsions were prepared which were stable after storage at room temperature for many months and which retained their microbicidal activity. A procedure was developed to manufacture up to 500 ml of 200 mM preconcentrated emulsions of monocaprin in tap water. The concentrates were clear and remained stable for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 22 publications
3
82
0
3
Order By: Relevance
“…Salmonella species were susceptible to caproic acid (Van Immerseel et al 2004) and caprylic acid (Skřivanová et al 2004). Thormar et al (2006) found that capric acid and monocaprin were more efficient against Campylobacter jejuni as compared with caprylic acid and monocaprylin, this observation having been confirmed by Molatová et al (2010). Depending on the monocaprylin concentrations and the temperatures examined, increasing temperature enhanced the bactericidal activity of monocaprylin, which can be partially explained by an increase in solubility.…”
Section: Dbm 3157mentioning
confidence: 78%
“…Salmonella species were susceptible to caproic acid (Van Immerseel et al 2004) and caprylic acid (Skřivanová et al 2004). Thormar et al (2006) found that capric acid and monocaprin were more efficient against Campylobacter jejuni as compared with caprylic acid and monocaprylin, this observation having been confirmed by Molatová et al (2010). Depending on the monocaprylin concentrations and the temperatures examined, increasing temperature enhanced the bactericidal activity of monocaprylin, which can be partially explained by an increase in solubility.…”
Section: Dbm 3157mentioning
confidence: 78%
“…Fatty acids, especially medium chain fatty acids, were found to have antimicrobial properties for a wide range of microorganisms (2,3,16,19,24,27). Recently, Thormar and coworkers (26) reported that monocaprin, the monoglyceride of capric acid, was effective in killing significant populations of C. jejuni in chicken feed. Caprylic acid is a medium chain fatty acid with eight carbons naturally found in breast milk, bovine milk, and coconut oil (12,13,16).…”
mentioning
confidence: 99%
“…In contrast, capric acid has been shown to have antimicrobial properties against other Gram-negative bacteria, including Campylobacter jejuni, Salmonella spp. and Escherichia coli (Thormar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%